The use of artificial intelligence in education in the light of security Culture according to the opinions of Hungarian and Turkish youth - Csiszárik-Kocsir, Ágnes; Revák, Bernadett (Edelweiss Applied Science and Technology, 2024)
Today, the importance of information security in education is increasingly emphasised. For members of generations X, Y and Alpha, ICT tools have become everyday objects of use, making it essential that teaching methods adapt and innovate accordingly. In particular, it is important that students learn to use data and devices safely, and the necessary guidelines should be integrated into the educational process. The six principles of security set out by the OECD apply to both students and teachers and provide guidance for users. Safety awareness is central to the development of a safety culture. In addition to knowledge and competences, safety culture also includes awareness and intentionality, which are essential for future success. There are many dimensions and aspects of awareness, but perhaps the most important in the context of education is the development of the digital dimension. However, it is also important to teach young people about the safe use of artificial intelligence and the limits of its applicability. The aim of our study is to examine how young people use the opportunities offered by digitalisation in educational institutions, with a particular focus on the use of AI and the perceptions and visions of its use. We will interpret this through an intercultural lens, comparing the intercultural characteristics and attitudinal differences of Hungarian and Turkish youth based on a questionnaire survey conducted in both countries.